On the meaning of the word choroba [‘disease’] in Józef Zmijewski’s handbook - Paluszak-Bronka, Anna (Papers in Linguistics, 2022)
The aim of the article is to reconstruct the meaning of the word choroba [Eng. disease] as used by Józef Zmijewski in his manuscript Metoda leczenia środkami dotąd nieużywanymi [Eng. A Method of Treatment with Means So Far Unused]. On the basis of injuries, conditions, symptoms, physiological and pathophysiological processes, as well as anatomical names that Zmijewski included in disease units, it is proved that the analyzed word differs both from definitions of disease recorded in dictionaries of the Polish language (SL, SW, SJPD) and its clinical explanations from the turn of the 18th and 19th centuries. Reasons for these discrepancies are also outlined. In relation to medical definitions, they may have resulted from Zmijewski’s socio-utilitarian understanding of disease, while in relation to explanations provided in dictionaries of the Polish language, these differences should be explained by the state of medical knowledge at the time, which influenced lexicographic definitions.